Experimental Investigations on TMI and IM-FWM in Distributed Side-Pumped Fiber Amplifier - Heng Chen; Jianqiu Cao; Zhihe Huang; Yuan Tian; Zhiyong Pan; Xiaolin Wang; Jinbao Chen (IEEE Photonics Journal)
The inter-modal four-wave mixing (IM-FWM) and transversal mode instabilities (TMI) are experimentally studied in high-power distributed side-pumped fiber amplifiers. To the best of our knowledge, we have made the first demonstration of TMI and IM-FWM which can be suppressed simultaneously by increasing the bending diameter. Besides, the experimental results show that the counter-pumping scheme is beneficial to suppress both of IM-FWM and TMI, when comparing with co-pumping scheme. Furthermore, these two effects cannot be observed when the M2 factor is lower than 1.3, which can give a condition to estimate whether these two effects should be considered or not. The pertinent study can provide some guidance for understanding TMI and IM-FWM in the high-power fiber laser and amplifier.